Analisis Kelayakan Usaha Sistem Methane Capture (Studi Kasus di PT Sukses Karya Sawit, Kalimantan Barat) - Marco Dignity Sianipar; Tuti Karyani; Ernah Ernah; Mahra Arari Heryanto (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
The treatment of Palm Oil Mill Effluent (POME) at PT SKS had conventionally been utilizing an open pond system. This system releases methane gas (CH4) into the atmosphere, contributing to greenhouse gas emissions. The emissions could be mitigated through the implementation of a methane capture system using a covered lagoon. This study analyzed the feasibility of the methane capture system at PT SKS by technical, social, economic, and environmental aspects, along with the development strategies. Economic feasibility featured financial parameters, such as Net Present Value (NPV) and Internal Rate of Return (IRR). The reduction of emission was calculated with AMS-III.H. Methane Recovery in Wastewater Treatment Version 19.0. SWOT matrix was used to formulate the development strategies. This research found that the methane capture system was feasible to implement. The system effectively converted POME biogas potential into electricity. The project created local employment. Economic analysis of the excess power business model was proved to be feasible with NPV = IDR 68.3 billion and IRR = 19.68%. The system reduced emissions by 11,077.63 tons CO2e/year. The priority development strategy was to prioritize biogas electricity for diesel fuel savings and optimize revenue through carbon credit trading.